Functional genetic analysis of mutations implicated in a human speech and language disorder. - Vernes, S; Nicod, J; Elahi, F; Coventry, J; Kenny, N; Coupe, A; Bird, L; Davies, K; Fisher, S (2006)
Mutations in the FOXP2 gene cause a severe communication disorder involving speech deficits (developmental verbal dyspraxia), accompanied by wide-ranging impairments in expressive and receptive language. The protein encoded by FOXP2 belongs to a divergent subgroup of forkhead-box transcription factors, with a distinctive DNA-binding domain and motifs that mediate hetero- and homodimerization. Here we report the first direct functional genetic investigation of missense and nonsense mutations in FOXP2 using human cell-lines, including a well-established neuronal model system. We focused on three unusual FOXP2 coding variants, uniquely identified in cases of verbal dyspraxia, assessing expression, subcellular localization, DNA-binding and transactivation properties. Analysis of the R553H forkhead-box substitution, found in all affected members of a large three-generation family, indicated that it severely affects FOXP2 function, chiefly by disrupting nuclear localization and DNA-binding properties. The R328X truncation mutation, segregating with speech/language disorder in a second family, yields an unstable, predominantly cytoplasmic product that lacks transactivation capacity. A third coding variant (Q17L) observed in a single affected child did not have any detectable functional effect in the present study. In addition, we used the same systems to explore the properties of different isoforms of FOXP2, resulting from alternative splicing in human brain. Notably, one such isoform, FOXP2.10+, contains dimerization domains, but no DNA-binding domain, and displayed increased cytoplasmic localization, coupled with aggresome formation. We hypothesize that expression of alternative isoforms of FOXP2 may provide mechanisms for post-translational regulation of transcription factor function.